2011
DOI: 10.3171/2010.11.jns10670
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical treatment of craniopharyngioma in adults and children: early and long-term results in a large case series

Abstract: Complete surgical removal of craniopharyngioma can be achieved with reasonable safety in more than 70% of patients. Recurrence of craniopharyngioma may occur even after apparent radical excision. Prompt management of residual or recurring disease by radiotherapy, repeat surgery, or a combination of both is usually successful in controlling further tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
179
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 226 publications
(199 citation statements)
references
References 35 publications
11
179
0
9
Order By: Relevance
“…23 The only study that examined the effect of surgery on QOL was by Mortini et al; however, only the Wen score was used and it was assigned retrospectively by the authors. 32 In that study, as in our study, Wen scores were shown to deteriorate. However, the accuracy of a retrospectively assigned Wen score by the treating physician may not be reliable.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…23 The only study that examined the effect of surgery on QOL was by Mortini et al; however, only the Wen score was used and it was assigned retrospectively by the authors. 32 In that study, as in our study, Wen scores were shown to deteriorate. However, the accuracy of a retrospectively assigned Wen score by the treating physician may not be reliable.…”
Section: Discussionsupporting
confidence: 55%
“…9 Treatment in the form of surgery, radiation, or both, has been implicated in further deterioration. 9,24,32 In assessing a patient's response to therapy, these traditional surgical end points, however, only tell a portion of the story. In addition to survival, progression-free survival, and morbidity, a patient's QOL is becoming increasingly important in assessment of therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations